2017
DOI: 10.20852/ntmsci.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the nonlinear heat transfer equation by AGM

Abstract: Abstract:In this paper, a novel nonlinear differential equation in the field of heat transfer has been investigated and solved completely by a new method that we called it Akbari-Ganjis Method (AGM). Regarding to the previously published papers, investigating this kind of equations is a very hard project to do and the obtained solution is not accurate and reliable. This issue will be appeared after comparing the obtained solution by Numerical Method or the Exact Solution. Based on the comparison which has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This method, which was created by Mirgolbabaee et al [24], is a great one for computing and can be used to solve many nonlinear differential equations. It assumes that the answer is a finite series, so it must be obtained by solving a series of algebraic problems.…”
Section: Akbari-ganji's Methods (Agm)mentioning
confidence: 99%
See 1 more Smart Citation
“…This method, which was created by Mirgolbabaee et al [24], is a great one for computing and can be used to solve many nonlinear differential equations. It assumes that the answer is a finite series, so it must be obtained by solving a series of algebraic problems.…”
Section: Akbari-ganji's Methods (Agm)mentioning
confidence: 99%
“…Among the many analytical methods for solving differential equations is the Akbari-Ganji approach, developed by Mirgolbabaee et al [24], applicable to a range of nonlinear ordinary and partial differential equations. Meanwhile, the Padé approximation, crafted by Henri Padé in 1890, optimizes the accuracy and convergence of solutions by approximating a function near a specific point [25].…”
Section: Introductionmentioning
confidence: 99%
“…Using Perturbed Collocation Method (PCM) [12] solved Singular Multi-order Fractional Differential Equations (SMFDE) of Lane-Emden Type with results which converged to the exact solutions. Akbari-Ganji Method (AGM) was used by [13], [14], [15] and [16] to find the numerical solution of differential equations arising from different physical problems. The studies concluded that AGM is a strong method to solve linear, nonlinear and partial differential equations, especially vibrational, wave and heat transfer problems.…”
Section: Introductionmentioning
confidence: 99%